Mental toughness and its relationship to the achievement level of the weightlifters in Egypt - Ahmet Aly; Ahmet Elemırı (Türk Spor ve Egzersiz Dergisi)
Mental Toughness (MT) is a crucial factor for super-elite athletes "Olympians", since differences in physical and technical competences are minimal at the professional level. A sample of 28 Egyptian male weightlifters (14 elite amp; 14 non-elite) and 18 female (9 elite amp; 9 non-elite) were selected to study the differences between the Egyptian elite and non-elite weightlifters. Also determine of the relationship between MT and the level of achievement was targeted. Participants completed the Mental Toughness Questionnaire (MTQ) evaluating an individual's competitive desire, focus, self-confidence, and resiliency (4 subscales). T-test and Pearson correlation coefficient were used for data analysis. MT of elite was significant than non-elite weightlifters (p  lt; 0.05, 2-tailed). Subscales associated with MT were also significant at elite. Focus and competitive desire were the most important psychological attributes characterizing the elite male weightlifters, while resilience and focus were at elite female. The correlation between MT and the achievement level was r =0.974** (p  lt; 0.01, 2-tailed). MT represents a condition for developing the achievement level. It is recommended that sport psychologists should help Egyptian elite weightlifters to develop and refine their MT to enter “high mental toughness range”, assisting with the formal integration of psychological training into physical training. As such, this integration may facilitate the effective transfer of mental skills into competition, which can help Egyptian weightlifters to achieve better results in great competitions (e.g., Olympic Games).